x+y=34
x-y=10
x=34-y
34-y-y=10
-2y=-24
y=12
Thus x=22
2007-05-25 07:13:14
·
answer #1
·
answered by The chemist 2
·
4⤊
0⤋
22+12=34
2007-05-25 14:12:59
·
answer #2
·
answered by MarshaMarsha 4
·
0⤊
0⤋
Let the first number be X
Let the second number be Y
X + Y = 34
X - Y = 10
if X - Y = 10 then X = 10 + Y
now, substitute:
(10 + Y) + Y = 34
2Y = 24
Y = 12
if Y = 12 then X = 22
proof:
12 + 22 = 34
22 - 12 = 10
2007-05-25 14:17:47
·
answer #3
·
answered by Roger S 7
·
1⤊
0⤋
34 - 10 = 24
24 / 2 = 12 (one of the numbers)
12 + 10 = 24 (second number)
Answer check:
12 + 24 = 34
2007-05-25 14:26:23
·
answer #4
·
answered by SWSprWmn 1
·
0⤊
0⤋
One number is 22, the other is 12.
2007-05-25 14:14:46
·
answer #5
·
answered by danw_tx 1
·
0⤊
0⤋
22 and 12
2007-05-25 14:12:43
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
x + y = 34
y = 34 - x
So sub that for y in the other equation.
x - y = 10
x - (34 - x) = 10
the negative makes everything in the parenthesis change when they are removed.
x - 34 + x = 10
2x = 10 + 34
2x = 44
x = 22
Now plug that in to the original equation.
x + y = 34
22 + y = 34
y = 12
SO x = 22, y = 12
2007-05-25 14:18:26
·
answer #7
·
answered by datgirl88 4
·
0⤊
0⤋
12 and 22.
2007-05-25 14:14:15
·
answer #8
·
answered by Awesome Bill 7
·
0⤊
0⤋
let x be the first number and y be the second number
x + y = 34
x - y = 10
add the two equtions
2x = 44
x = 22
22 + y = 34
x = 12
the two numbers are 12 and 22
2007-05-25 14:14:37
·
answer #9
·
answered by 7
·
1⤊
0⤋
x + y = 34
x - y = 10
x - (34 - x) = 10
2x - 34 = 10
2x = 44
x = 22
y = 22 - 10
y = 12
2007-05-25 14:13:39
·
answer #10
·
answered by mark r 4
·
3⤊
0⤋
x + y = 34
x - y = 10
------------- +
2x = 44
x = 22
Substitute x to ANY equation'
22 + y = 34
y = 34-22
=12
22 and 12
2007-05-27 10:53:18
·
answer #11
·
answered by wangsacl 4
·
0⤊
0⤋